1997
DOI: 10.1136/jnnp.62.3.239
|View full text |Cite
|
Sign up to set email alerts
|

Proton magnetic resonance spectroscopy in Parkinson's disease and progressive supranuclear palsy.

Abstract: Objectives-Proton magnetic resonance spectroscopy ('H-MRS)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(29 citation statements)
references
References 23 publications
3
24
0
2
Order By: Relevance
“…Found in all areas of the brain, it is the second most abundant amino acid in the central nervous system after glutamate (Clark, 1998;Tallan et al, 1956). It has been used clinically as a measure of neuronal or mitochondrial integrity, and decreased concentration of NAA is found in many neurodegenerative diseases Federico et al, 1997;Godbolt et al, 2006). The precise role of NAA continues to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Found in all areas of the brain, it is the second most abundant amino acid in the central nervous system after glutamate (Clark, 1998;Tallan et al, 1956). It has been used clinically as a measure of neuronal or mitochondrial integrity, and decreased concentration of NAA is found in many neurodegenerative diseases Federico et al, 1997;Godbolt et al, 2006). The precise role of NAA continues to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Although the first 1 H-MRS study published in patients with neurodegenerative parkinsonism suggested that 1 H-MRS of striatal structures might differentiate parkinsonian syndromes by virtue of reduced N-acetylaspartate/ creatine ratios in MSA but not Parkinson's disease [75], further MRS studies have shown reduced N-acetylaspartate/creatine and N-acetylaspartate/choline ratios in the lentiform nucleus or striatum not only in APD, but also in Parkinson's disease [73,[76][77][78]. Technical factors such as MRS techniques including different echoand relaxation times, voxel sizes and pulse sequences used in the different studies may be responsible for some of the variation of results seen in the published literature on 1 H-MRS for the differential diagnosis of neurodegenerative parkinsonism [73,78].…”
Section: Magnetic Resonance Spectroscopymentioning
confidence: 98%
“…1 H-MRS has been widely used to study the metabolism of relevant brain regions for PD such as the basal ganglia [19][20][21][22][23], motor cortex [22,24], temporoparietal cortex [21,25], posterior cingulate gyrus [26] and occipital lobe [27]. In addition, a number of spectroscopic studies of rodent [28][29][30][31] and/or non-human primate model [32] for PD have been reported.…”
Section: Introductionmentioning
confidence: 99%